Digital Literacy Assistance for Women at Madrasah Technology Al-Khwarizmi Pangalengan, Bandung Regency - Ridwan Rustandi (Prosperity: Journal of Society and Empowerment, 2022)
This study aims to analyze the process of digital literacy education and assistance for women at Madrasah Teknologi Al-Khwarizmi Pangalengan, Bandung Regency. Specifically, the research focuses on four aspects of digital literacy: digital skills, digital culture, digital ethics, and digital safety. The analysis uses a constructivist paradigm with a qualitative approach. Data were collected through observation, interviews, FGD, LGD, and documentation. Meanwhile, the mentoring process is carried out using an asset-based community development (ABCD) approach. The results of the research and mentoring show that the Madrasah of Technology Al-Khwarizmi is a non-formal educational institution in rural areas that focuses on providing understanding and assistance in digital literacy, especially for women. In addition, digital literacy assistance for women is carried out through increasing computer skills as a preventive measure against digital threats, positive cultural habituation by studying and reading the Qur'an in internet activities, strengthening digital ethics through family counseling and moral development for parents and community involvement and partnership networks in maintaining internet awareness.